(untitled) (Altre Modernità, 2012)
Jean Libis, Fabio Ferreira, Catherine Gublin, Sarah Mezaguer (eds.), Les Lectures de Gaston Bachelard. Index bibliographique (Paris, Presse Universitaire de Franche-Comté, 2011 ISBN: 978-2-84867-392) di Aurosa Alison